Handling manuscript submission, revision and acceptance: a young author’s guide - Kumar, Mahendra; Jeet, Kiron (International Journal Of Community Medicine And Public Health, 2026)
Publishing research in reputable journals is a challenging yet rewarding process that demands patience, persistence, and continuous learning. Manuscript rejection is a common experience in academic publishing, with rejection rates in many indexed journals ranging from 80% to 95%. Despite this, rejection should not be viewed as failure. This paper explores the common reasons for manuscript rejection and provides practical guidance for young researchers to improve their chances of publication success. Key areas discussed include selecting an appropriate journal, assessing journal quality, understanding journal scope, and carefully following author guidelines. The article also highlights the importance of strong scientific writing, clear titles, effective abstracts, structured introductions, and rigorous methodology. Main focus is placed on constructive handling of reviewer feedback and maintaining professionalism after rejection. Finally, successful scientific publishing depends on careful preparation, clarity, resilience, and dedication to producing high-quality research that contributes meaningfully to the scientific community.